Boymom eaudiobook Reimagining boyhood in the age of impossible masculinity. - Whippman, Ruth (Books on Tape, 2024)
Combining painfully honest memoir, cultural analysis, and reporting, BoyMom is a humorous and heartbreaking deep dive into the complexities of raising boys in our fraught political moment. “Rapist, school-shooter, incel, man-child, interrupter, mansplainer, boob-starer, birthday forgetter, frat boy, dude-bro, homophobe, self-important stoner, emotional-labor abstainer, non-wiper of kitchen counters. Trying to raise good sons suddenly felt like a hopeless task.”    As the culture wars rage, and masculinity has been politicized from all sides, feminist writer and mother of three boys Ruth Whippman finds herself conflicted and scared. While the right pushes a dangerous vision of fantasy manhood, her feminist peers often dismiss boys as little more than entitled predators-in-waiting.  Meanwhile her home life feels like a daily confrontation with the triumph of nature over nurture.     With young men in the grip of a loneliness epidemic and dying by suicide at a rate of nearly four times their female peers, Whippman asks: How do we raise our sons to have a healthy sense of self without turning them into privileged assholes? How can we find a feminism that holds boys to a higher standard but still treats them with empathy? And what do we do when our boys won’t cooperate with our plans?   Whippman digs into the impossibly contradictory pressures boys now face; and the harmful blind spots of male socialization that are leaving boys isolated, emotionally repressed, and adrift. Feminist gonzo-style, she spends months interviewing incels, reports on a conference for boys accused of sexual assault; crashes at a residential therapy center for young men in Utah, talks to a wide range of psychologists and other experts, and gets boys of all backgrounds to open up about sex, consent, porn, body image, mental health, cancel culture, screens, friendship and loneliness. Along the way, she finds her simple certainties about male privilege seriously challenged.    With wit, honesty, and a refusal to settle for easy answers, BoyMom charts a new path to give boys a healthier, more expansive, and fulfilling story about their own lives.